How language shapes anti-fat bias: comparing the effects of disease and fat-rights framing - Rook, Ella D.; Holmes, Kevin J. (Frontiers in Communication, 2023)
Being fat is often described as a "disease"-a form of linguistic framing that may exacerbate bias against fat people rather than reduce it as intended. Framing fatness as a matter of equal treatment and respect ("fat rights") may be more effective for bias reduction. In a preregistered experiment (N = 401), we directly compared the effects of disease and fat-rights framing on attitudes toward fat people. Participants read a news article that affirmed or negated (a) the claim that fatness is a disease and (b) the unacceptability of weight discrimination, and then expressed their attitudes toward fat people. Disease-affirming articles yielded more negative attitudes than disease-negating articles, but only for participants who explicitly recognized that the article influenced their attitudes. For these participants, fat-rights framing also had a significant impact: those who read a disease-affirming article expressed less negative attitudes toward fat people when the article also affirmed rather than negated fat rights. These results show that language can shift public opinion about fatness when people are aware of its persuasive power. Our findings support a social-pragmatic account of linguistic framing and have implications for real-world anti-bias efforts.